2014
DOI: 10.3390/e16084322
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion-Zone Dynamics Explored with Microfluidics and Optical Tweezers

Abstract: Abstract:The exclusion zone (EZ) is a boundary region devoid of macromolecules and microscopic particles formed spontaneously in the vicinity of hydrophilic surfaces. The exact mechanisms behind this remarkable phenomenon are still not fully understood and are debated. We measured the short-and long-time-scale kinetics of EZ formation around a Nafion gel embedded in specially designed microfluidic devices. The time-dependent kinetics of EZ formation follow a power law with an exponent of 0.6 that is strikingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…surface charge density, porosity, Donnan equilibrium quantities, etc ) concerning the nanoporous material as well as the nanoscale ion exchange process. Hence, the natural ion depletion phenomenon induced by the ion exchange has been drawn significant attentions recently 22 , 25 31 , 33 , 34 . Despite the fact that the proton inside the medium is being dissociated by the absorbed water from the outer solution as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…surface charge density, porosity, Donnan equilibrium quantities, etc ) concerning the nanoporous material as well as the nanoscale ion exchange process. Hence, the natural ion depletion phenomenon induced by the ion exchange has been drawn significant attentions recently 22 , 25 31 , 33 , 34 . Despite the fact that the proton inside the medium is being dissociated by the absorbed water from the outer solution as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Using laser tweezers, a forcefield has been measured inside the exclusion zone. Two independent experiments have found that the magnitude of the repulsive force decays as a function of distance from the surface in a manner consistent with the diffusiophoresis theory [ 1 , 3 ]. The presence of a force decaying from the surface is inconsistent with the theory that a new phase forms in the exclusion zone.…”
Section: Alternative Explanations For Ez Phenomenamentioning
confidence: 53%
“…Further experiments and a computational study using COMSOL Multiphysics simulation by Esplandiu et al lend further support to the findings of Florea et al [ 11 ]. Huszár et al note that the growth of the exclusion zone with times follows a power law with an exponent of 0.6, very close to the exponent of 0.5 expected for a diffusion-driven process [ 3 ]. Using laser tweezers, a forcefield has been measured inside the exclusion zone.…”
Section: Alternative Explanations For Ez Phenomenamentioning
confidence: 67%
See 2 more Smart Citations